2016
DOI: 10.7287/peerj.preprints.2482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Being in the zone: Using behavioral and EEG recordings for the indirect assessment of flow

Abstract: As such, video games are enjoyed most when the level and speed of the game match the players' skills. An optimal balance between challenges and skills triggers the subjective experience of "flow", a focused motivation leading to a feeling of spontaneous joy. Here we present the validation of a novel technique to indirectly assess the extent to which subjects experience flow during real game play by assessing attentional engagement; first behaviorally and in a second stage by means of electroencephalogram (EEG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
6
1
Order By: Relevance
“…Participants played the shooter game Counter-Strike: Global Offensive under three conditions (under-challenged, flow, and over-challenged) both in a 2D and a VR set-up while they were simultaneously asked to respond to the oddball sounds. Their results did not replicate the outcome of the previous study by Castellar et al (2016) , as they reported slower reaction times and more errors in the flow condition. A marginally significant posterior mid-line P300 amplitude was recorded during VR compared to playing in 2D during the flow condition.…”
Section: Survey Methodologycontrasting
confidence: 76%
See 2 more Smart Citations
“…Participants played the shooter game Counter-Strike: Global Offensive under three conditions (under-challenged, flow, and over-challenged) both in a 2D and a VR set-up while they were simultaneously asked to respond to the oddball sounds. Their results did not replicate the outcome of the previous study by Castellar et al (2016) , as they reported slower reaction times and more errors in the flow condition. A marginally significant posterior mid-line P300 amplitude was recorded during VR compared to playing in 2D during the flow condition.…”
Section: Survey Methodologycontrasting
confidence: 76%
“…Castellar and colleageus utilized an auditory oddball paradigm as a secondary task to investigate attention while subjects played a game as a primary task ( Castellar et al, 2016 ). Participants were requested to play the game Star Reaction in under-challenged, flow, and over-challenged conditions while simultaneously responding to a rare sound in the auditory oddball task.…”
Section: Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, electroencephalogram (EEG) and FMRi are the most commonly used techniques to measure CNS responses (Valenza et al, 2016). In addition, EEG has been used to measure engagement (Castellar, E Voigt A., Jan N. & Marinazzo, D.& Looy, 2016;Cirett Galán & Beal, 2012;Shestyuk et al, 2019) and it can detect the perceived cognitive absorption (Conrad & Bliemel, 2016;Léger et al, 2014). Changes on cardiovascular dynamics by specific emotional states (Marín-Morales et al, 2019) can be measured using electrocardiogram devices (ECG).…”
Section: Physiological Devices For Experience Assessmentmentioning
confidence: 99%
“…For example, Yun et al (2017) found that flow peaked after 25 min of game playing. Hence, the player may require time to transition from explicit to implicit control and to allocate attentional resources that will make him/her resistant to distractions (e.g., Jackson and Csikszentmihalyi, 1999 ; Jennett, 2010 ; Bavelier et al, 2012 ; Nuñez Castellar et al, 2016 ). Although similar observations have not been proposed for immersion, the conceptual overlap between flow and immersion ( Brown and Cairns, 2004 ; Jennett et al, 2008b ) suggests that mutual substrates are at play.…”
Section: A Comparison Between Flow and Immersionmentioning
confidence: 99%